Establishing molecular pathology curriculum for pathology trainees and continued medical education: a collaborative work from the Molecular Pathology Study Group of the Korean Society of Pathologists - Jiwon Koh; Ha Young Park; Jeong Mo Bae; Jun Kang; Uiju Cho; Seung Eun Lee; Haeyoun Kang; Min Eui Hong; Jae Kyung Won; Youn-La Choi; Wan-Seop Kim; Ahwon Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Background The importance of molecular pathology tests has increased during the last decade, and there is a great need for efficient training of molecular pathology for pathology trainees and as continued medical education. Methods The Molecular Pathology Study Group of the Korean Society of Pathologists appointed a task force composed of experienced molecular pathologists to develop a refined educational curriculum of molecular pathology. A 3-day online educational session was held based on the newly established structure of learning objectives; the audience were asked to score their understanding of 22 selected learning objectives before and after the session to assess the effect of structured education. Results The structured objectives and goals of molecular pathology was established and posted as a web-based interface which can serve as a knowledge bank of molecular pathology. A total of 201 pathologists participated in the educational session. For all 22 learning objectives, the scores of self-reported understanding increased after educational session by 9.9 points on average (range, 6.6 to 17.0). The most effectively improved items were objectives from next-generation sequencing (NGS) section: 'NGS library preparation and quality control' (score increased from 51.8 to 68.8), 'NGS interpretation of variants and reference database' (score increased from 54.1 to 68.0), and 'whole genome, whole exome, and targeted gene sequencing' (score increased from 58.2 to 71.2). Qualitative responses regarding the adequacy of refined educational curriculum were collected, where favorable comments dominated. Conclusions Approach toward the education of molecular pathology was refined, which would greatly benefit the future trainees.